Localization of Iranian Architectural Model in Low-Cost Housing Production Technology (Tehran) - Bargh, Farshad Hatami; Mansouri, Behrouz; Zare, leila (MAJ - Malaysia Architectural Journal, 2023)
One of the important points in achieving sustainable development is providing welfare and comfort and security in the society to emphasize the necessity of overcoming poverty. Localization of the low-cost housing model plan is significant in facilitating the aforementioned process in the face of population growth. The studies of the history of housing industrialization and construction technology emphasize the principle of reducing cost and increasing quality and speed. Therefore, in order to obtain optimal results from the study of housing projects in Islamic and developing countries and their comparisons to obtain suitable points and finally the effectiveness of Iranian architectural indicators, we can reach the desired results in providing a suitable model of low-cost housing in this research. The research method in this article is analytical-descriptive. The projects of Iraq, India and Singapore have been used in the study.